Are We Ready to Measure Skin Permeation of Modern Antiaging GHK–Cu Tripeptide Encapsulated in Liposomes? - Karolina Ogórek; Kinga Nowak; Emilia Wadych; Lena Ruzik; Andrei R. Timerbaev; Magdalena Matczuk (Molecules)
Cosmetically active compounds (CACs), both of lipophilic and hydrophilic origin, have difficulty reaching the deeper layers of the skin, and this shortcoming significantly reduces their efficacy. One such CAC that occurs naturally in the human body and displays many beneficial properties (via reducing fine lines and wrinkles, tightening skin, improving its elasticity, etc.) is the glycyl-L-histidyl-L-lysine tripeptide complex of copper (GHK–Cu). GHK–Cu is a fairly hydrophilic compound with limited permeation through the lipophilic stratum corneum. On the other hand, liposomes capable of encapsulating GHK–Cu may improve its permeation potential. The present review discusses various issues related to obtaining insight into the permeation of CACs through the skin. Methods for studying the transport of CACs encapsulated by liposomes and free GHK–Cu across the skin barrier are summarized. An analysis of the literature data reveals that the transport of liposomes containing GHK–Cu received little attention. This research gap gives an impetus to the methodological developments for assessing the effect of liposomes on GHK–Cu transportation and trafficking.